Port site metastasis after robotic assisted laparoscopic radical prostatectomy: Diagnosis via prostate-specific membrane antigen (PSMA)-targeted 18F-DCFPyL PET/CT - Joon Yau Leong; Maria J. D'Amico; Courtney E. Capella; Leonard G. Gomella; Joseph K. Izes (Urology Case Reports, 2025)
We present a case of port site metastasis (PSM) that was identified in an 82-year-old man with an elevated prostate-specific antigen (PSA) to 3.9 ng/mL, concerning for biochemical recurrence after robotic-assisted radical prostatectomy, adjuvant radiation, and six months of androgen deprivation therapy with an undetectable PSA post-treatment over 10 years ago. A 2.1 cm solitary tracer avid nodule on the right lateral abdominal wall with no other evidence of recurrence or metastatic disease was found on prostate-specific membrane antigen (PSMA)–targeted 18F-DCFPyL PET/CT scan. The patient underwent local excision of this metastatic lesion, and final pathology revealed metastatic prostatic adenocarcinoma.